Innocent [Until] Proven Guilty! Bearing the Stigma of ‘the Corrupt’ under Accountability Trials in Pakistan - Lughmani, Muhammad Saqib Anjum; Abdullah, Muhammad Tanweer (Governance and Society Review, 2023)
This study focuses on a key drawback of the public sector accountability scenario in Pakistan. It touches upon the implications faced by public sector officials due to poor implementation of accountability laws and regulations. It emphasizes the possible reasons in terms of why and how accountability outcomes produce a ‘stigma’ for persons who face trial and are not found guilty, instead of bringing in some betterment. It also discusses the wide ranging implications of the stigma, characterized by social rejection, cultural alienation, political and economic marginalization, and loss of career development opportunity, especially in the event when such stigma is induced by ‘media trials’ of sub judice cases. The authors also attempt to establish how the weak, ineffective, and politically-driven accountability mechanisms in Pakistan lead the public sector in not making any progress under accountability regulations. Several institutional ‘systemic’ factors that appear to have cause-effect relationships — characterized as a ‘vicious circle’, are identified. Some conclusions are also drawn and recommendations made regarding future policy and organizations to help de-stigmatize accountability regulations.